2020
DOI: 10.3390/prosthesis2030018
|View full text |Cite
|
Sign up to set email alerts
|

Zein/Bioactive Glass Coatings with Controlled Degradation of Magnesium under Physiological Conditions: Designed for Orthopedic Implants

Abstract: Magnesium and its alloys are widely considered as temporary bio-implants owing to their mechanical properties and biocompatibility. However, the high corrosion rates and degradation in the physiological environment restrict the practical application of Mg as a biomedical device. Therefore, in this study, Zein/45S5 bioactive glass (BG) coatings were deposited via electrophoretic deposition (EPD) on pretreated pure magnesium (Mg) substrates, which controls the rapid degradation of magnesium. The set of EPD param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Furthermore, the signal intensity of Ca and P showed a strong increase with the increase in the incubation period. Thus, the SEM/EDX results indicated that a new phase with the chemical composition similar to HA developed on the surface of the multi‐structured coatings 40,41 . The HA is developed on the coatings owe to the heterogeneous nucleation.…”
Section: Resultsmentioning
confidence: 91%
“…Furthermore, the signal intensity of Ca and P showed a strong increase with the increase in the incubation period. Thus, the SEM/EDX results indicated that a new phase with the chemical composition similar to HA developed on the surface of the multi‐structured coatings 40,41 . The HA is developed on the coatings owe to the heterogeneous nucleation.…”
Section: Resultsmentioning
confidence: 91%
“…The pH here increases due to the presence of OH − ions. Overall, positively charged zein/Ag-Sr doped MBGNs get attracted towards the cathode, and, along with the OH − ions, become unstable and get deposited on the cathode [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…After 21 days, the results indicated that the corrosion rate of samples immersed in EBSS buffered with sodium bicarbonate was similar to that obtained in vivo. In addition to EBSS, cell culture media, such as DMEM and MEM, are preferable to investigate the corrosion behavior of Mg-based biomaterials [88][89][90].…”
Section: Mg Corrosion In Simulated Body Environmentsmentioning
confidence: 99%